Pelatihan dan Pemberdayaan UMKM di Kota Pangkal Pinang melalui Digital Marketing - Fithriawan Nugroho; Aditya Ahmad Fauzi; Faishal Farras; Nidia Mindiyarti; Muhammad Iqbal Hanafi; Siti Kamilah (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Pangkalpinang City play a strategic role in the regional economy, yet only 30% have optimally utilized digital marketing. This community service program aims to enhance the digital literacy of MSME entrepreneurs through digital marketing training, covering the use of social media, marketplaces, and customer data analysis. The methods employed include a participatory approach, practice-based training, and intensive mentoring. The implementation results indicate a significant increase in the utilization of digital platforms by MSMEs, with 90% of participants successfully optimizing social media, 75% actively using marketplaces, and 85% leveraging Google My Business. Additionally, there was an average revenue increase of 20-30% within three months after the training. This program demonstrates that digital marketing adoption can enhance MSME competitiveness, promote cost efficiency in promotions, and foster a sustainable digital community.